2017
DOI: 10.1038/s41598-017-14242-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic measurement of near-field radiative heat transfer

Abstract: Super-Planckian near-field radiative heat transfer allows effective heat transfer between a hot and a cold body to increase beyond the limits long known for black bodies. Until present, experimental techniques to measure the radiative heat flow relied on steady-state systems. Here, we present a dynamic measurement approach based on the transient plane source technique, which extracts thermal properties from a temperature transient caused by a step input power function. Using this versatile method, that require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
0
24
1
Order By: Relevance
“…Recent evidence has also shown that HTLV-1 inserts an ectopic CTCF binding site forming loops between the provirus and host genome, altering expression of proviral and host genes ( 42 ). CTCF has also been shown to promote HSV-1 lytic transcription by facilitating the elongation of RNA Pol II and preventing silenced chromatin on the viral genome ( 43 ). Moreover, one can speculate that having a CTCF motif can not only help in maintaining viral genome confirmation but can also help insulate the chromatin activity of the neighborhood wherein the virus inserts into the host genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has also shown that HTLV-1 inserts an ectopic CTCF binding site forming loops between the provirus and host genome, altering expression of proviral and host genes ( 42 ). CTCF has also been shown to promote HSV-1 lytic transcription by facilitating the elongation of RNA Pol II and preventing silenced chromatin on the viral genome ( 43 ). Moreover, one can speculate that having a CTCF motif can not only help in maintaining viral genome confirmation but can also help insulate the chromatin activity of the neighborhood wherein the virus inserts into the host genome.…”
Section: Discussionmentioning
confidence: 99%
“…
Recently, many works have experimentally demonstrated near-field radiative heat transfer (NFRHT) exceeding the far-field blackbody limit between planar surfaces [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Due to the difficulties associated with maintaining the nanosize gaps required for measuring a nearfield enhancement, these demonstrations have been limited to experiments that cannot be implemented into actual applications.
…”
mentioning
confidence: 99%
“…However, their measurements were not convincing mainly due to the lack of capability in achieving a subwavelength vacuum gap separation. This technical difficulty has been addressed by placing micro/nano-spacers between planar structures as a practical and cost-effective way to achieve a subwavelength gap spacing between large plates [2,16,[32][33][34][35][36][37]. However, undesired heat conduction through spacer-plate contacts prevents a direct measurement of near-field thermal radiation, often necessitating tedious post-processing to exclude the heat conduction contribution from the measurement.…”
mentioning
confidence: 99%